INFORMATION GAP: SPEAK FLUENTLY IS BETTER IN EFL CONTEXT - Mushoffan Prasetianto (UIBU, 2019)
This paper aimed to review small talk technique proposed by Hunter (2012) and to propose information gap. Small talk is another way of corrective feedback. The teacher gives feedback after the activity is done by giving them written feedback/worksheet. The feedback is given to develop the students’ accuracy and speaking complexity ability. However, the question on how accurate the students, whether students are expected to be native-like or not, emerges. In EFL context, it is hard to make the students to be native-like since English is foreign language for them. The naturalness of environment does not give language input for them. Thus, students can speak fluently is better than speak accurately in EFL context. As long as, the students can deliver the message, it is enough for them because the purpose of communication is to deliver the missing information between speakers. The information gap technique is the way to develop the students’ fluency. This technique provides the real communication which is delivering the missing information. In conclusion, students should speak fluently in EFL context.